EFFICIENCY ANALYSIS OF PRIVATE SECTOR BANKS IN INDIA USING DEA APPROACH - K. , Muthyalappa; K. , Pushpanjali (International Journal of Psychosocial Rehabilitation, 2017)
This study examines the efficiency of private sector banks in India using the Data Envelopment Analysis (DEA) approach. DEA is a non-parametric method employed to assess the relative efficiency of decision-making units (DMUs) by comparing multiple inputs and outputs. The analysis covers a selection of major private sector banks in India over a specified period, 2016-17, providing a comprehensive evaluation of their operational efficiency. The study utilizes the Constant Returns to Scale (CRS) to determine efficiency scores, with a focus on input minimization. The analysis highlights the importance of effective resource utilization and strategic management in enhancing bank efficiency. Furthermore, inefficient banks are provided with benchmarks and potential pathways for improvement by learning from their more efficient peers. This study contributes to the existing literature on banking efficiency in India and offers valuable insights for bank managers, policymakers, and regulators aiming to enhance the performance and competitiveness of the Indian banking sector.